(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Every social and global issue is a business occasion just staying for the right kind of inventive Entrepreneurship, the right kind of investment, the right kind of collaborative action. Peter Drucker The end of this paper is to understand the impact of services marketing 7P’s( Product or Service, Price, Place, Promotion, People, Physical substantiation, Process) in the negotiating of competitive advantage against marketing 4P’s. ultramodern marketing companies are blending all the 7Ps of services selling in their marketing conditioning to retain being guests as well as to attract implicit bones in Indian Market. A significant body of literature has revealed that the 4Ps of the marketing blend have radiate under diminishment by numerous marketing scholars from different perspectives. For services businesses, the customary marketing blend frame should be dragged to include the other 3Ps( people, process and physical substantiation) as deliberate foundations, which torture companies ’ enactment.